COVID-19 mRNA vaccine immune response to the addition of osteopathic manipulative treatment with lymphatic pumps: a randomized controlled trial - Eric S. Martinez; Sebastien Fuchs; Hendrik Szurmant; Xunxuan Chen; Andrew Comer; Edward Lee; Raymond Hruby; Rebecca Giusti; Brian Loveless; Julieanne P. Sees; Paula Crone; Laura J. Peek; et al. (Virus Research)
Osteopathic manipulative treatment (OMT) has demonstrated immune augmentation in preclinical studies, but direct evidence in humans is lacking. We conducted a randomized controlled trial on the addition of OMT in subjects receiving their first Pfizer-BioNTech (BNT162b2) COVID-19 vaccination in 2021. Subjects were randomized to either receive OMT at each vaccination or not. We measured anti-spike protein, anti-nucleocapsid, and neutralizing antibodies. Primary endpoints were time-resolved and cumulative anti-SARS-CoV-2 spike protein antibody titers. Secondary endpoints were breakthrough infection symptom frequency, severity, and duration. 104 subjects were randomly assigned to control or OMT group, with 91 subjects completing the primary vaccination series. Initial antibody titers separated subjects into 51 COVID-19-naïve and 40 COVID-19-pre-exposed. COVID19-naïve subjects were selected for analysis based on data homogeneity. In this cohort, the OMT group showed significantly increased anti-SARS-CoV-2 spike protein antibody titers at 3 weeks vs controls (p = 0.038). Cumulative titers in this cohort, were significantly increased in the OMT group at 5 weeks (p = 0.046) and at 13 weeks (p = 0.009) compared to controls. An intention-to-treat (ITT) analysis of all subjects revealed significant differences in titers between the OMT group and controls at 3 weeks (p < 0.001) and at 13 weeks for AUC titers (p = 0.035) as compared to controls. The COVID-19- pre-exposed group showed no significant differences. Both groups had 10 breakthrough infections, but the OMT group experienced fewer and less severe symptoms, with symptom duration reduced from 8 days in controls to 4.5 days in the OMT group (p = 0.013). Medication duration was shorter in the OMT group, 1.5 days vs 5 days (p = 0.014). OMT-treated subjects developed quicker and stronger vaccine-induced antibody titers and had significantly shorter and less severe breakthrough symptoms, suggesting OMT may enhance immune responses to COVID19 vaccination.